The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/jpn.12917
|View full text |Cite
|
Sign up to set email alerts
|

Physiological changes in the adenosine deaminase activity, antioxidant and inflammatory parameters in pregnant cows and at post‐partum

Abstract: The aim of this study was to evaluate the behaviour of adenosine deaminase (ADA) activity, as well as its participation in the immunomodulation of pregnant cows. Thus, sixteen cows were divided into two groups (A and B): the group A was composed by cows not pregnant (n = 8), while the group B was composed by pregnant cows (n = 8). Serum levels of interleukin-10 (IL-10), IL-6, tumour necrosis factor alpha (TNF-α), reactive oxygen species (ROS) and C-reactive protein (CRP), as well as ADA and glutathione S-trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In our study, calving significantly increased ADA1 isoenzyme in both serum and saliva. An increase of ADA in serum after calving had been previously described [43], and therefore ADA has been proposed to be a marker of a proinflammatory status of the animal due to calving [44]. To the authors' knowledge, this is the first report in which salivary ADA has been also reported to increase after calving in cows, being this change of higher magnitude of that reported in serum.…”
Section: Discussionmentioning
confidence: 51%
“…In our study, calving significantly increased ADA1 isoenzyme in both serum and saliva. An increase of ADA in serum after calving had been previously described [43], and therefore ADA has been proposed to be a marker of a proinflammatory status of the animal due to calving [44]. To the authors' knowledge, this is the first report in which salivary ADA has been also reported to increase after calving in cows, being this change of higher magnitude of that reported in serum.…”
Section: Discussionmentioning
confidence: 51%
“…The occurrence in ammatory response during the parturition process has previously been described for sows [29,30], mares [31], cows [32] and humans [33]. Due to the signi cant changes observed in ADA1, ADA2 and tADA activities throughout the periparturient period in both the PDS + and the PDS ÷ sows, saliva ADA seems to re ect this in ammatory response in sows.…”
Section: Discussionmentioning
confidence: 67%
“…Another explanation could be in ammation-related synthesis of ADA, as suggested by our results. The relation to in ammation is, however, not entirely clear, as although Fávero et al [32] demonstrated increased ADA activities in cows at the end of pregnancy and after calving, other reports were not able to demonstrate any increase in serum ADA during in ammatory conditions [22,23].…”
Section: Discussionmentioning
confidence: 93%
“…Pei et al (2018) suggest that A2AR plays a role in tissue in lammation, which is attributable to A2AR proin lammatory activation. The signi icant high level of ADA serum level in adenosine group compared to control one can support this role of adenosine since that ADA released principally by in lammatory cell (Lee et al, 2020) and its activity has important role as in lammatory modulators (Fávero et al, 2018). Adenosine is closely connected to the A2AR activation (Al-Moula et al, 2012) an increased extracellular adenosine concentration promotes the up regulation of A2AR signaling that enhance the synthesis of in lammatory mediators like IL-1b (Meng et al, 2019), suggesting that adenosine enhances in lammatory response via A2AR-mediated signaling.…”
Section: Resultsmentioning
confidence: 78%